Structural Characteristics of Carbon Nanotubes Fabricated Using Simple Spray Pyrolysis Method - Khairurrijal Khairurrijal; Mikrajuddin Abdullah; Memoria Rosi; Fatimah A. Noor (Indonesian Journal of Physics, 2008)
A simple spray pyrolysis method has successfully used to synthesize carbon nanotubes (CNTs). Their structural characteristics were characterized by employing field-emission scanning electron microscopy (FE-SEM), energy dispersive X-ray (EDX) analysis, and X-ray diffraction (XRD) methods. FE-SEM images confirmed that the diameters of CNTs were in the range of 20 to 80 nm. The average diameter of CNTs increased considerably as the growth temperature increased (above 700 oC). The changes in growth time and ferrocene mass altered the average diameter of CNTs slightly. EDX analysis and XRD patterns indicated that Fe2O3 and Fe3O4, which originate from the oxidation of ferrocene catalyst, are the main impurities of the CNTs. The concentrations of Fe2O3 and Fe3O4 became lower and higher, respectively, for the growth temperatures higher than 700°C because Fe2O3 is the most stable at high temperatures.